Answer:
The equation y = -6x + 1 represents the line ⇒ A
Explanation:
The form of the linear equation is y = m x + b, where
The rule of the slope is m =
, where
- (x1, y1) and (x2, y2) are two points lie on the line
∵ The line passes through points (1, -5) and (3, -17)
∴ x1 = 1 and y1 = -5
∴ x2 = 3 and y2 = -17
→ Substitute them in the rule of the slope to find it
∵ m =
=
=
= -6
∴ m = -6
→ Substitute it in the form of the equation above
∴ y = -6x + b
→ To find b substitute x by 1 and y by -5 in the equation
∵ -5 = -6(1) + b
∴ -5 = -6 + b
→ Add 6 to both sides
∴ 1 = b
→ Substitute it in the equation
∴ y = -6x + 1
∴ The equation y = -6x + 1 represents the line